Sensibilidade de Monilinia fructcola a grupos de fungicidas em pessegueiro - Tortelli, Brenda (2025)
Monilinia fructicola is an important phytopathogen in peach orchards, causing the disease known as brown rot. Chemical control is the most commonly used method to manage the disease, but several reports of fungicide resistance have emerged. Succinate dehydrogenase inhibitor (SDHI) fungicides may offer a new option for disease control. The objectives of this study were to confirm the phenotypes of 75 M. fructicola isolates from Brazil against the fungicides mancozeb (MZ), iprodione (IP), thiophanate-methyl (TF), tebuconazole (TEB), and azoxystrobin (AZ) using discriminatory doses; to establish the baseline sensitivity of these isolates to SDHI fungicides based on EC50 values; and to analyze the sensitivity of a recent population from the state of Rio Grande do Sul (RS) to the same fungicides. Additionally, the sensitivity of M. fructicola isolates from two production regions (Araucária/PR and Paranapanema/SP) was characterized, highlighting the importance of in-field phenotyping for accurate recommendations. The stability of phenotypes from these two regions was also evaluated after four years of storage. This study established a baseline sensitivity for SDHI fungicides in Brazilian M. fructicola isolates, providing a reference for developing anti-resistance management strategies and monitoring sensitivity to carboxamide, a newly introduced active ingredient for brown rot control. The results reinforce the recommendation of SDHI fungicides by RS growers for effective disease management, in combination with MZ, IP, TF, and AZ, which also showed no reduction in sensitivity among the analyzed isolates. Furthermore, the study demonstrated that phenotypic variability may be influenced by environmental conditions and phytosanitary management practices in each region, emphasizing the need for frequent monitoring of isolate sensitivity to fungicides to optimize control strategies, particularly for tebuconazole. Regarding the impact of prolonged storage of M. fructicola isolates on filter paper, after four years, this practice was found to potentially alter isolate sensitivity to fungicides.